Analisis Struktur Kalimat Majemuk dalam Berita “Mahasiswa UGM Raih Penghargaan Kompetisi Formula Internasional 2024” pada laman Kompas - Destiawati, Dela; Della Apriliani, Salza; Khoirunnisa, Niha; Lisnawati, Iis (Kopula: Jurnal Bahasa, Sastra, dan Pendidikan, 2025)
This study aims to analyze the structure of compound sentences in the news titled "UGM Students Win the 2024 International Formula Competition Award". This analysis was carried out to identify the form and pattern of the compound sentence structure in conveying information effectively. The method used in this study is by using a qualitative descriptive method with syntactic analysis techniques. The results of this study indicate that the news compound sentences are used to connect more complex ideas such as cause-effect relationships, additional information, and contrast. Compound sentences in this news can rely on coordinating conjunctions such as the words "and", "but", and the word "but" to clarify the relationship between events. In the use of this compound sentence can play an important role in maintaining the continuity of information, enriching the narrative, and improving the readability of the news text. This research is expected to contribute to the understanding of the syntactic structure of news texts in the context of the Indonesian language.